Assessing costs of a hypertension program in primary care: evidence from the HEARTS program in Mexico - Carlos Chivardi; Brian Hutchinson; Virginia Molina; Elena Moreno; Ileana Fajardo; Gloria P. Giraldo-Arcila; Hugo Miguel Malo; Pedro Ordunez; Roxana Rodríguez-Franco; Andrew E. Moran; Deliana Kostova (Pan American Health Organization, 2022)
Objective. In 2021, Mexico launched the HEARTS program to improve the prevention and control of cardiovascular disease (CVD) risk factors in 20 primary care facilities in the states of Chiapas and Yucatán. This study projects the annual cost of program implementation and discusses budgetary implications for scaling up the program. Methods. We obtained district-level data on treatment protocols, medication costs, and other resources required to prevent and treat CVD. We used the HEARTS Costing Tool to estimate total and per-patient costs. A "partial implementation" scenario calculated the costs of implementing HEARTS if existing pharmacological treatment protocols are left in place. The second scenario, "full implementation," examined costs if programs use HEARTS pharmacological protocol. Results. Respectively in the partial and full implementation scenarios, total annual costs to implement and operate HEARTS were $260 023 ($32.1 per patient/year) and $255 046 ($31.5 per patient/year) in Chiapas, and $1 000 059 ($41.3 per patient/year) and $1 013 835 ($43.3 per patient/year) in Yucatán. In Chiapas, adopting HEARTS standardized treatment protocols resulted in a 9.7 % reduction in annual medication expenditures relative to maintaining status-quo treatment approaches. In Yucatán, adoption was $12 875 more expensive, in part because HEARTS hypertension treatment regimens were more intensive than status quo regimens. Conclusion. HEARTS in the Americas offers a standardized strategy to treating and controlling CVD risk factors. In Mexico, approaches that may lead to improved program affordability include adoption of the recommended HEARTS treatment protocols with preferred medications and task shifting of services from physicians to nurses and other providers.